2022
DOI: 10.3389/fphys.2022.896951
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial translocator protein deficiency exacerbates pathology in acute experimental ulcerative colitis

Abstract: In human patients and animal models of ulcerative colitis (UC), upregulation of the mitochondrial translocator protein (TSPO) in the colon is consistent with inflammation. Although the molecular function for TSPO remains unclear, it has been investigated as a therapeutic target for ameliorating UC pathology. In this study, we examined the susceptibility of Tspo gene-deleted (Tspo−/−) mice to insults as provided by the dextran sodium sulfate (DSS)-induced acute UC model. Our results show that UC clinical signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…Overall, TSPO expression is increased in biopsies from IBD patients compared to healthy controls. In a more recent study, the authors observed that Tspo knock-out mice had a more severe disease upon treatment with DSS [70]. Interestingly, knock-out and wild-type mice showed a different modulation of genes involved in mast cell (cd34 and mcp6), macrophage (F4/80) and dendritic (cd11c) cell function, as well as TNFα.…”
Section: Role Of Mitochondria In the Immune Systemmentioning
confidence: 95%
“…Overall, TSPO expression is increased in biopsies from IBD patients compared to healthy controls. In a more recent study, the authors observed that Tspo knock-out mice had a more severe disease upon treatment with DSS [70]. Interestingly, knock-out and wild-type mice showed a different modulation of genes involved in mast cell (cd34 and mcp6), macrophage (F4/80) and dendritic (cd11c) cell function, as well as TNFα.…”
Section: Role Of Mitochondria In the Immune Systemmentioning
confidence: 95%